Battle of the borders: Is a range-extending fiddler crab affecting the spatial niche of a congener species? - Arakaki, Jonathann Yukio [UNESP]; Grande, Fernando Rafael De [UNESP]; Arvigo, Alexandre Luiz [UNESP]; Pardo, Juan Carlos Farias [UNESP]; Fogo, Bruno Rafael [UNESP]; Sanches, Fábio H.C. [UNESP]; Miyai, Caio Akira [UNESP]; Marochi, Murilo Zanetti [UNESP]; Costa, Tânia Marcia [UNESP] (Elsevier, 2020)
Climate change is drastically altering environmental conditions and resource availability. Many organisms are shifting their distribution boundaries. Fiddler crabs, for instance, are important ecosystem engineers in coastal environments that have been extending their distribution range poleward. In this study, we evaluated the influence of a range-extending species, Leptuca cumulanta, which has recently overlapped the distribution of the resident species Leptuca uruguayensis. Through a set of field and laboratory experiments, we characterised the degree of territorial overlap between L. cumulanta and L. uruguayensis from the lower to upper intertidal zone in a mangrove area. We also analysed whether the presence of L. cumulanta prevents habitat choosiness or influences agonistic behaviours in L. uruguayensis in territorial fights. We found that both species overlap territories at the same level in the intertidal zone. However, we observed that both habitat choice and agonistic behaviours of L. uruguayensis were unresponsive to the presence of L. cumulanta. The low interference between recent heterospecific neighbours sharing the same space supports coexistence of fiddler crabs L. uruguayensis and L. cumulanta in the early stage of overlapping.
Keywords: Distribution; Interspecific interactions; Leptuca cumulanta; Leptuca uruguayensis; Territory overlap